Twelve distinct laboratory methods used to measure SARS-CoV-2 in wastewaters throughout a three-year Ontario-wide, Canada study: Impact on public health interpretation of disease incidence - Nada Hegazy; K. Ken Peng; Johanna de Haan-Ward; Elizabeth Renouf; Elizabeth Mercier; Shen Wan; X. Joan Hu; Charmaine Dean; Mark Servos; Elizabeth Edwards; Gustavo Ybazeta; Marc Habash; et al. (Journal of Water Process Engineering, 2026)

Investigating the contributions of herbaceous vegetation biomass to soil accretion in Louisiana's coastal deltaic wetlands using airborne imaging spectroscopy - Daniel Jensen; Elena Solohin; Edward Castañeda-Moya; Marc Simard; David R. Thompson; Cathleen E. Jones; Alexandra Christensen; Andre Rovai; Andy Fontenot; Robert Twilley (Remote Sensing of Environment, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Delta-X: An airborne remote sensing framework to calibrate hydrodynamic and ecogeomorphic processes responsible for land building in coastal deltas - Marc Simard; Cathleen E. Jones; Robert R. Twilley; Edward Castañeda-Moya; Sergio Fagherazzi; Cédric G. Fichot; Michael P. Lamb; Paola Passalacqua; Tamlin M. Pavelsky; David R. Thompson; Saoussen Belhadj-aissa; Pradipta Biswas; et al. (Remote Sensing of Environment, 2026)

Performance evaluation and methods comparison of transcriptomic-based approaches for the characterization of wastewater treatment effluent - Adam D. Biales; Morgan S. Hu; David C. Bencic; Mary Jean See; Susan T. Glassmeyer; Edward T. Furlong; Julia M. Stelman; Weichun Huang; Dana W. Kolpin; Marc A. Mills; Laura D. Brunelle; Angela L. Batt; et al. (Environmental Pollution, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Corrigendum to ‘Passive sampling, a practical method for wastewater-based surveillance of SARS-CoV-2’ [Environ. Res., 204 Part-B (2022) 112058] - Jemaneh Habtewold; David McCarthy; Edward McBean; Ilya Law; Larry Goodridge; Marc Habash; Heather M. Murphy (Environmental Research, 2025)

Vertebral elemental composition reveals ontogenetic changes in habitat use in a Northeast Atlantic mesopredator shark - Neil D. Cook; Ana Samperiz; Morten Andersen; Edward Inglis; Marc-Alban Millet; Jo Cable; Sarah E. Perkins (Estuarine, Coastal and Shelf Science, 2025)

Global energy consumption of water treatment technologies - Michele Magni; Edward R. Jones; Marc F.P. Bierkens; Michelle T.H. van Vliet (Water Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Green solutions for treating groundwater polluted with nitrates, pesticides, antibiotics, and antibiotic resistance genes for drinking water production - Jessica Subirats; Edward J. Pastor-López; Joan Pascó; Marlene Mendoza; Miriam Guivernau; Belén Fernández; Rosa Trobajo; Marc Viñas; Carme Biel; David Sánchez; Jofre Herrero; Victor Matamoros (Journal of Environmental Management, 2025)

Co-occurrence and correlation of arsenic, cadmium, and lead in processed foods intended for infants and young children: evaluation of two statistical approaches adapted to censored data and their implications for risk management - Sarah I. Murphy; Régis Pouillot; Marc Boyer; Sherri Dennis; Eileen Abt; Patrick Gray; Dwayne Jarman; Edward Nyambok; Jane M. Van Doren (Food Additives & Contaminants: Part A, 2025)

Investigating the chemical space coverage of multiple chromatographic and ionization methods using non-targeted analysis on surface and drinking water collected using passive sampling - Angela L. Batt; Laura D. Brunelle; Natalia S. Quinete; Eva K. Stebel; Brian Ng; Piero Gardinali; Alex Chao; Anna K. Huba; Susan T. Glassmeyer; David A. Alvarez; Dana W. Kolpin; Edward T. Furlong; et al. (Science of The Total Environment, 2024)

Flood prevention benefits provided by Canadian natural ecosystems - Gabriela T. Duarte; Richard Schuster; Marc Edwards; Camille O. Dallaire; Ágnes Vári; Matthew G.E. Mitchell (Ecosystem Services, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Pyrrhotites in asteroid 162173 Ryugu: Records of the initial changes on their surfaces with aqueous alteration - Hiroharu Yui; Shu-hei Urashima; Morihiko Onose; Mayu Morita; Shintaro Komatani; Izumi Nakai; Yoshinari Abe; Yasuko Terada; Hisashi Homma; Kazuko Motomura; Kiyohiro Ichida; Tetsuya Yokoyama; et al. (Geochimica et Cosmochimica Acta, 2024)

Emotional and functional well-being in long-term breast cancer survivorship - Yumeng Ren; Joanna Maselko; Xianming Tan; Andrew F. Olshan; Angela M. Stover; Antonia V. Bennett; Katherine E. Reeder-Hayes; Jessie K. Edwards; Bryce B. Reeve; Melissa A. Troester; Marc A. Emerson (Cancer Causes & Control, 2024)

Drinking water sources, quality, and associated health outcomes in Appalachian Virginia: A risk characterization study in two counties - Alasdair Cohen; Md Rasheduzzaman; Bethesda O'Connell; Teresa Brown; Mami Taniuchi; Leigh-Anne Krometis; Alan Hubbard; Phillip Scheuerman; Marc Edwards; Amanda Darling; Blaine Pennala; Sarah Price; et al. (International Journal of Hygiene and Environmental Health, 2024)

Olenekian sulfur isotope records: Deciphering global trends, links to marine redox changes and faunal evolution - Oluwaseun Edward; Jorge E. Spangenberg; Marc Leu; Charline Ragon; Sandrine Le Houedec; Aymon Baud; Hugo Bucher; Torsten Vennemann (Chemical Geology, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

Attribution of fine particulate matter and ozone health impacts in Canada to domestic and US emission sources - Amanda J. Pappin; Nick Charman; Marika Egyed; Phil Blagden; Annie Duhamel; Jessica Miville; Ivana Popadic; Patrick M. Manseau; Guillaume Marcotte; Rabab Mashayekhi; Jacinthe Racine; Robyn Rittmaster; et al. (Science of The Total Environment, 2024)

Understanding the initial use stage of cement mortar lining in drinking water distribution systems: Silicon and aluminum as stability indicators - Qiaozhi Liu; Yuan Zhuang; Guiwei Li; Yao Zhang; Marc A. Edwards; Baoyou Shi (Journal of Environmental Sciences, 2024)

Evidence for variable provenance of Mercury anomalies during the Smithian–Spathian (Olenekian) - Oluwaseun Edward; Marc Leu; Hugo Bucher; Sandrine Le Houedec; Franziska Blattmann; Christian Vérard; Thierry Adatte; Aymon Baud; Jeroen E. Sonke; Torsten Vennemann (Global and Planetary Change, 2024)

Evaluation of four human-associated fecal biomarkers in wastewater in Southern Ontario - Charles Chettleburgh; Sean Xiao Ma; Megan Swinwood-Sky; Hanlan McDougall; Devita Kireina; Gurleen Taggar; Edward McBean; Valeria Parreira; Lawrence Goodridge; Marc Habash (Science of The Total Environment, 2023)

Global responses to the COVID-19 pandemic by recreational anglers: considerations for developing more resilient and sustainable fisheries - J. Robert Britton; Adrian C. Pinder; Josep Alós; Robert Arlinghaus; Andy J. Danylchuk; Wendy Edwards; Kátia M. F. Freire; Casper Gundelund; Kieran Hyder; Ivan Jarić; Robert Lennox; Wolf-Christian Lewin; et al. (Reviews in Fish Biology and Fisheries, 2023)
The global COVID-19 pandemic resulted in many jurisdictions implementing orders restricting the movements of people to inhibit virus transmission, with recreational angling often either not permitted or access to fisheries and/or related infrastructure being prevented. Following the lifting of restrictions, initial angler surveys and licence sales suggested increased participation and effort, and altered angler demographics, but with evidence remaining limited. Here, we overcome this evidence gap by identifying temporal changes in angling interest, licence sales, and angling effort in world regions by comparing data in the ‘pre-pandemic’ (up to and including 2019); ‘acute pandemic’ (2020) and ‘COVID-acclimated’ (2021) periods. We then identified how changes can inform the development of more resilient and sustainable recreational fisheries. Interest in angling (measured here as angling-related internet search term volumes) increased substantially in all regions during 2020. Patterns in licence sales revealed marked increases in some countries during 2020 but not in others. Where licence sales increased, this was rarely sustained in 2021; where there were declines, these related to fewer tourist anglers due to movement restrictions. Data from most countries indicated a younger demographic of people who participated in angling in 2020, including in urban areas, but this was not sustained in 2021. These short-lived changes in recreational angling indicate efforts to retain younger anglers could increase overall participation levels, where efforts can target education in appropriate angling practices and create more urban angling opportunities. These efforts would then provide recreational fisheries with greater resilience to cope with future global crises, including facilitating the ability of people to access angling opportunities during periods of high societal stress.

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Observation of the Coastal Areas, Estuaries and Deltas from Space - Benoit Laignel; Stefano Vignudelli; Rafael Almar; Mélanie Becker; Abderrahim Bentamy; Jérôme Benveniste; Florence Birol; Frédéric Frappart; Deborah Idier; Edward Salameh; Marcello Passaro; Melisa Menende; et al. (Surveys in Geophysics, 2023)
Coastal regions (including estuaries and deltas) are very complex environments with diverse hydrodynamic and bio-geomorphological contexts and with important socio-economic and ecological problems. These systems are among the most affected by human impact through urbanization and port activities, industrial and tourism activities. They are directly affected by the impact of climate change on sea level, storm surges frequency and strength, as well as recurrence of coastal river floods. A sustainable future for coastal zones depends on our capacity to implement systematic monitoring with focus on: (1) forcings affecting coastal zones at different spatio-temporal scales (sea level rise, winds and waves, offshore and coastal currents, tides, storm surges, river runoff in estuaries and deltas, sediment supply and transport, vertical land motions and land use); (2) morphological response (e.g., shoreline migration, topographical changes). Over the last decades, remote sensing observations have contributed to major advances in our understanding of coastal dynamics. This paper provides an overview of these major advances to measure the main physical parameters for monitoring the coastal, estuarine and delta environments and their evolution, such as the water level and hydrodynamics near the shoreline, water/sediment contact (i.e., shoreline), shoreline position, topography, bathymetry, vertical land motion, bio-physical characteristics of sediments, water content, suspended sediment, vegetation, and land use and land cover.

Beach erosion aggravates the drastic decline in marine turtle populations in French Guiana - Damien Chevallier; Marc Girondot; Christina Péron; Jordan Martin; Marc Bonola; Johan Chevalier; Benoît de Thoisy; Laurent Kelle; Yvon Le Maho; Antoine Gardel; Edward J. Anthony (Regional Environmental Change, 2023)
Yalimapo beach, near the Maroni River estuary in French Guiana, is an important turtle nesting site. The interaction of massive mud banks migrating alongshore from the distant Amazon River with discharge from the Maroni River generates strong beach morpho-sedimentary changes. The eventual degradation of the marine turtle nesting habitats resulting from these changes represents a threat to the offspring, and consequently, to the turtle population. Field operator counts of green and leatherback turtle nests were combined with high-resolution topographic measurements of the beach over four field surveys in 2012 and 2014 to map the topographic modifications susceptible to affect nesting on Yalimapo beach. We assumed that the survival of nests was at stake when the depth of sand between the egg chamber and the topographic surface (i.e. the top) of the beach was < 50 cm, and that beach surface lowering > 10 cm represented unfavourable conditions for nest safety with unequal nest survival across the beach. Erosion of the beach surface exceeding a depth of 50 cm therefore results in nest destruction. Digital elevation models were produced to quantify the topographic modification of nesting on Yalimapo beach and highlight the endangered nesting areas. As the modification of the beach is not linear, some sectors are more eroded than others, resulting in unequal nest survival across the beach. Overall, up to 40% of the nests were presumed destroyed over the 2 years of survey, but true losses would depend on the species and the preferential locations of their nesting habitats. The relatively unfavourable conditions that prevailed during the 2 years of the survey are consistent with persistent erosion of Yalimpao beach since 2011. This ongoing erosion could explain in part the drastic decline of the leatherback turtle population in western French Guiana over the period 2001–2018. The substrate quality and dynamics of the nesting beach in relation to the preferred nesting habitat of each species are therefore critical issues that should be considered in the conservation strategies of marine turtles. The beach nesting conditions of marine turtles in French Guiana, as elsewhere, could be further aggravated in the future by climate change effects, including sea-level rise.

Pilot-scale assessment reveals effects of anode type and orthophosphate in governing antimicrobial capacity of copper for Legionella pneumophila control - Yang Song; Amy Pruden; William J Rhoads; Marc A Edwards (Water Research, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

The effects of resistance exercise on appetite sensations, appetite related hormones and energy intake in hormone receptor-positive breast cancer survivors - Sarah A. Purcell; Edward L. Melanson; Anosheh Afghahi; Virginia F. Borges; Isabella Sinelli; Marc-Andre Cornier (Appetite, 2023)

Streptomyces spiramenti sp. nov., isolated from a deep-sea microbial mat - Rachel M. Loughran; Caitlin M. Diefendorf; Jassmine R. Reill-VanSise; Edward A. Mitchell; Oliver B. Vining; David A. Gallegos; Gregory Miller; Marc J. Koyack; David K. Oline; Orion S. Rivers; Blake Ushijima; Jimmy H. Saw; et al. (Archives of Microbiology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Guiding principles for rewilding - Steve Carver; Ian Convery; Sally Hawkins; Rene Beyers; Adam Eagle; Zoltan Kun; Erwin Van Maanen; Yue Cao; Mark Fisher; Stephen R. Edwards; Cara Nelson; George D. Gann; et al. (Conservation Biology, 2021)
There has been much recent interest in the concept of rewilding as a tool for nature conservation, but also confusion over the idea, which has limited its utility. We developed a unifying definition and 10 guiding principles for rewilding through a survey of 59 rewilding experts, a summary of key organizations’ rewilding visions, and workshops involving over 100 participants from around the world. The guiding principles convey that rewilding exits on a continuum of scale, connectivity, and level of human influence and aims to restore ecosystem structure and functions to achieve a self‐sustaining autonomous nature. These principles clarify the concept of rewilding and improve its effectiveness as a tool to achieve global conservation targets, including those of the UN Decade on Ecosystem Restoration and post‐2020 Global Biodiversity Framework. Finally, we suggest differences in rewilding perspectives lie largely in the extent to which it is seen as achievable and in specific interventions. An understanding of the context of rewilding projects is the key to success, and careful site‐specific interpretations will help achieve the aims of rewilding.

Geomorphology of a tropical river delta under pressure: the Rufiji delta, Tanzania—context, channel connectivity and alongshore morpho-sedimentary and hydrodynamic variability - Edward J. Anthony; Manon Besset; Florin Zainescu; Marc Goichot (Geo-Marine Letters, 2021)

Glucocorticoid Receptor Activation Restores Learning Memory by Modulating Hippocampal Plasticity in a Mouse Model of Brain Vitamin B12 Deficiency - Natacha Dreumont; Khalid Mimoun; Carine Pourié; Edward V. Quadros; Jean-Marc Alberto; Rémy Umoret; Déborah Helle; Aurélie Robert; Jean-Luc Daval; Jean-Louis Guéant; Grégory Pourié (Molecular Neurobiology, 2021)

An update of the Worldwide Integrated Assessment (WIA) on systemic insecticides. Part 2: impacts on organisms and ecosystems - Lennard Pisa; Dave Goulson; En-Cheng Yang; David Gibbons; Francisco Sánchez-Bayo; Edward Mitchell; Alexandre Aebi; Jeroen van der Sluijs; Chris J. K. MacQuarrie; Chiara Giorio; Elizabeth Yim Long; Melanie McField; et al. (Environmental Science and Pollution Research, 2021)
New information on the lethal and sublethal effects of neonicotinoids and fipronil on organisms is presented in this review, complementing the previous Worldwide Integrated Assessment (WIA) in 2015. The high toxicity of these systemic insecticides to invertebrates has been confirmed and expanded to include more species and compounds. Most of the recent research has focused on bees and the sublethal and ecological impacts these insecticides have on pollinators. Toxic effects on other invertebrate taxa also covered predatory and parasitoid natural enemies and aquatic arthropods. Little new information has been gathered on soil organisms. The impact on marine and coastal ecosystems is still largely uncharted. The chronic lethality of neonicotinoids to insects and crustaceans, and the strengthened evidence that these chemicals also impair the immune system and reproduction, highlights the dangers of this particular insecticidal class (neonicotinoids and fipronil), with the potential to greatly decrease populations of arthropods in both terrestrial and aquatic environments. Sublethal effects on fish, reptiles, frogs, birds, and mammals are also reported, showing a better understanding of the mechanisms of toxicity of these insecticides in vertebrates and their deleterious impacts on growth, reproduction, and neurobehaviour of most of the species tested. This review concludes with a summary of impacts on the ecosystem services and functioning, particularly on pollination, soil biota, and aquatic invertebrate communities, thus reinforcing the previous WIA conclusions (van der Sluijs et al. 2015).

Human aflatoxin exposure in Uganda: Estimates from a subset of the 2011 Uganda AIDS indicator survey (UAIS) - Nicholas C. Zitomer; Abigael O. Awuor; Marc-Alain Widdowson; Johnni H. Daniel; Maya R. Sternberg; Michael E. Rybak; Edward K. Mbidde (Food Additives & Contaminants: Part A, 2021)

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

A review of American lobster (Homarus americanus) records around the British Isles: 2012 to 2018 - Christopher John Barrett; Alastair Cook; David Stone; Chris Evans; Debbie Murphy; Paul Johnson; Marc Thain; Gabrielle Wyn; Mark Grey; Hugh Edwards; Declan Quigley; Paul Douglas Stebbing (Hydrobiologia, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Factors determining variation in colour morph frequencies in invasive Harmonia axyridis populations - Alois Honek; Peter M. J. Brown; Zdenka Martinkova; Jiri Skuhrovec; Marek Brabec; Giovanni Burgio; Edward W. Evans; Marc Fournier; Audrey A. Grez; Jan Kulfan; Francesco Lami; Eric Lucas; et al. (Biological Invasions, 2020)

The importance of naturally attenuated SARS‐CoV ‐2 in the fight against COVID ‐19 - Jean Armengaud; Agnès Delaunay‐Moisan; Jean‐Yves Thuret; Eelco van Anken; Diego Acosta‐Alvear; Tomás Aragón; Carolina Arias; Marc Blondel; Ineke Braakman; Jean‐François Collet; René Courcol; Antoine Danchin; et al. (Environmental Microbiology, 2020)
The current SARS‐CoV‐2 pandemic is wreaking havoc throughout the world and has rapidly become a global health emergency. A central question concerning COVID‐19 is why some individuals become sick and others not. Many have pointed already at variation in risk factors between individuals. However, the variable outcome of SARS‐CoV‐2 infections may, at least in part, be due also to differences between the viral subspecies with which individuals are infected. A more pertinent question is how we are to overcome the current pandemic. A vaccine against SARS‐CoV‐2 would offer significant relief, although vaccine developers have warned that design, testing and production of vaccines may take a year if not longer. Vaccines are based on a handful of different designs (i), but the earliest vaccines were based on the live, attenuated virus. As has been the case for other viruses during earlier pandemics, SARS‐CoV‐2 will mutate and may naturally attenuate over time (ii). What makes the current pandemic unique is that, thanks to state‐of‐the‐art nucleic acid sequencing technologies, we can follow in detail how SARS‐CoV‐2 evolves while it spreads. We argue that knowledge of naturally emerging attenuated SARS‐CoV‐2 variants across the globe should be of key interest in our fight against the pandemic.

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Frag SAD : A database of diversity and species abundance distributions from habitat fragments - Jonathan M. Chase; Mario Liebergesell; Alban Sagouis; Felix May; Shane A. Blowes; Åke Berg; Enrico Bernard; Berry J. Brosi; Marc W. Cadotte; Luis Cayuela; Adriano G. Chiarello; Jean‐Francois Cosson; et al. (Ecology, 2019)
Habitat destruction is the single greatest anthropogenic threat to biodiversity. Decades of research on this issue have led to the accumulation of hundreds of data sets comparing species assemblages in larger, intact, habitats to smaller, more fragmented, habitats. Despite this, little synthesis or consensus has been achieved, primarily because of non‐standardized sampling methodology and analyses of notoriously scale‐dependent response variables (i.e., species richness). To be able to compare and contrast the results of habitat fragmentation on species’ assemblages, it is necessary to have the underlying data on species abundances and sampling intensity, so that standardization can be achieved. To accomplish this, we systematically searched the literature for studies where abundances of species in assemblages (of any taxa) were sampled from many habitat patches that varied in size. From these, we extracted data from several studies, and contacted authors of studies where appropriate data were collected but not published, giving us 117 studies that compared species assemblages among habitat fragments that varied in area. Less than one‐half (41) of studies came from tropical forests of Central and South America, but there were many studies from temperate forests and grasslands from all continents except Antarctica. Fifty‐four of the studies were on invertebrates (mostly insects), but there were several studies on plants (15), birds (16), mammals (19), and reptiles and amphibians (13). We also collected qualitative information on the length of time since fragmentation. With data on total and relative abundances (and identities) of species, sampling effort, and affiliated meta‐data about the study sites, these data can be used to more definitively test hypotheses about the role of habitat fragmentation in altering patterns of biodiversity. There are no copyright restrictions. Please cite this data paper and the associated Dryad data set if the data are used in publications.

Transgenic maize phosphoenolpyruvate carboxylase alters leaf–atmosphere CO2 and 13CO2 exchanges in Oryza sativa - Rita Giuliani; Shanta Karki; Sarah Covshoff; Hsiang-Chun Lin; Robert A. Coe; Nuria K. Koteyeva; Marc A. Evans; W. Paul Quick; Susanne von Caemmerer; Robert T. Furbank; Julian M. Hibberd; Gerald E. Edwards; et al. (Photosynthesis Research, 2019)

Caspase-8 restricts natural killer cell accumulation during MCMV Infection - Yanjun Feng; Lisa P. Daley-Bauer; Linda Roback; Marc Potempa; Lewis L. Lanier; Edward S. Mocarski (Medical Microbiology and Immunology, 2019)

Joint exposure to smoking, excessive weight, and physical inactivity and survival of ovarian cancer patients, evidence from the Ovarian Cancer Association Consortium - Albina N. Minlikeeva; Rikki Cannioto; Allan Jensen; Susanne K. Kjaer; Susan J. Jordan; Brenda Diergaarde; J. Brian Szender; Kunle Odunsi; Hani Almohanna; Paul Mayor; Kirsten Starbuck; Emese Zsiros; et al. (Cancer Causes & Control, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Contrasting genetic structure of sympatric congeneric gastropods: Do differences in habitat preference, abundance and distribution matter? - Edward J. G. Wort; Mark A. Chapman; Stephen J. Hawkins; Lucy Henshall; Alfonso Pita; Marc Rius; Suzanne T. Williams; Phillip B. Fenberg (Journal of Biogeography, 2019)
Aim The relationship of population genetics with the ecology and biogeography of species may be explored by comparing phenotypically similar but ecologically different congeners with overlapping ranges. We compared genetic differentiation between two congeneric rocky intertidal gastropods across a major portion of their sympatric range. We hypothesized that the habitat generalist with high abundance and continuous distribution would exhibit comparatively less genetic differentiation than the habitat specialist with low abundance and a fragmented distribution. Location North‐east Atlantic from the north‐west Iberian Peninsula to southern British coastline. Taxon Gastropoda, Trochidae, Steromphala (formerly Gibbula ). Methods Field surveys were conducted to assess the presence/absence and the abundance of Steromphala umbilicalis (generalist) and S. pennanti (specialist) at 23 localities along ~1,800 km coastline. We isolated polymorphic microsatellite markers for both species (seven loci for S. umbilicalis and eight for S. pennanti ) and used these to genotype 187 S. umbilicalis and 157 S. pennanti individuals. We used standard population genetic analyses to compare patterns of genetic differentiation between species in relation to the field surveys. Results Steromphala pennanti showed a more fragmented distribution, significantly lower abundance, and greater genetic differentiation than S. umbilicalis . One S. umbilicalis population towards the north of the range (southern Britain) was genetically distinct from all other sampled populations. Steromphala pennanti showed greater genetic differentiation between three southern localities, which may be attributable to its fragmented distribution and lower abundance because of limited availability of its preferred fucoid habitat in this region. We also suggest that oceanographic currents could be associated with regional genetic structure. Main conclusions The habitat generalist showed high‐local abundances, continuous distribution and low regional genetic differentiation. We found the opposite pattern for the habitat specialist. Our study highlights the importance of considering ecological (e.g. abundance, habitat preferences) and abiotic variables (e.g. ocean currents and temperature) for understanding differences in genetic structure of sympatrically distributed congeners.

Evaluating and implementing social–ecological systems: A comprehensive approach to sustainable fisheries - Robert L. Stephenson; Stacey Paul; Melanie Wiber; Eric Angel; Ashleen J. Benson; Anthony Charles; Omer Chouinard; Marc Clemens; Dan Edwards; Paul Foley; Lindsay Jennings; Owen Jones; et al. (Fish and Fisheries, 2018)
Fisheries sustainability is recognized to have four pillars: ecological, economic, social (including cultural) and institutional (or governance). Although international agreements, and legislation in many jurisdictions, call for implementation of all four pillars of sustainability, the social, economic and institutional aspects (i.e., the “human dimensions”) have not been comprehensively and collectively addressed to date. This study describes a framework for comprehensive fisheries evaluation developed by the Canadian Fisheries Research Network ( CFRN ) that articulates the full spectrum of ecological, economic, social and institutional objectives required under international agreements, together with candidate performance indicators for sustainable fisheries. The CFRN framework is aimed at practical fisheries evaluation and management and has a relatively balanced distribution of elements across the four pillars of sustainability relative to 10 alternative management decision support tools and indicator scorecards, which are heavily focused on ecological and economic aspects. The CFRN framework has five immediate uses: (a) It can serve as a logic frame for defining management objectives; (b) it can be used to define alternate management options to achieve given objectives; (c) it can serve as a tool for comparing management scenarios/options in decision support frameworks; (d) it can be employed to create a report card for comprehensive fisheries management evaluation; and (e) it is a tool for practical implementation of an integrated social–ecological system approach.

OXI1 kinase plays a key role in resistance of Arabidopsis towards aphids (Myzus persicae) - Tahsin Shoala; Martin G. Edwards; Marc R. Knight; Angharad M. R. Gatehouse (Transgenic Research, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Sea trout (Salmo trutta) growth patterns during early steps of invasion in the Kerguelen Islands - Marc Jarry; Edward Beall; Patrick Davaine; François Guéraud; Philippe Gaudin; Jean-Christophe Aymes; Jacques Labonne; Matthias Vignon (Polar Biology, 2018)

History of hypertension, heart disease, and diabetes and ovarian cancer patient survival: evidence from the ovarian cancer association consortium - Albina N. Minlikeeva; Jo L. Freudenheim; Rikki A. Cannioto; J. Brian Szender; Kevin H. Eng; Francesmary Modugno; Roberta B. Ness; Michael J. LaMonte; Grace Friel; Brahm H. Segal; Kunle Odunsi; Paul Mayor; et al. (Cancer Causes & Control, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Inherent variability in lead and copper collected during standardized sampling - Sheldon Masters; Jeffrey Parks; Amrou Atassi; Marc A. Edwards (Environmental Monitoring and Assessment, 2016)

Molecular mechanisms of D-cycloserine in facilitating fear extinction: insights from RNAseq - Stefanie Malan-Müller; Lorren Fairbairn; Willie M. U. Daniels; Mahjoubeh Jalali Sefid Dashti; Edward J. Oakeley; Marc Altorfer; Martin Kidd; Soraya Seedat; Junaid Gamieldien; Sîan Megan Joanna Hemmings (Metabolic Brain Disease, 2016)

Cosmogenic dating of Late Pleistocene glaciation, southern tropical Andes, Peru - Jeremy D. Shakun; Peter U. Clark; Shaun A. Marcott; Edward J. Brook; Nathaniel A. Lifton; Marc Caffee; William R. Shakun (Journal of Quaternary Science, 2015)
We present 30 10 Be dates on three moraines formed by small glaciers in the southern tropical Andes of Peru to determine the timing of the local Last Glacial Maximum (LGM) and subsequent deglaciation. Two terminal moraines indicate that the local LGM ended at 23.5 ± 0.5 and 21.2 ± 0.8 ka, or well before the end of the global LGM (20–19 ka). A recessional moraine perched at the base of a steep valley wall has a 10 Be age of 19.8 ± 0.3 ka, suggesting that glaciers had largely retreated from the area during the earliest stages of the last termination and before the onset of the deglacial CO 2 rise and increase in tropical sea surface temperatures. These ages generally agree with other tropical glacial chronologies and reflect a broad synchroneity between low‐ and high‐latitude deglaciation at the LGM, but the trigger for early deglaciation of the tropics remains unclear.

Worldwide impacts of climate change on energy for heating and cooling - Maryse Labriet; Santosh R. Joshi; Marc Vielle; Philip B. Holden; Neil R. Edwards; Amit Kanudia; Richard Loulou; Frédéric Babonneau (Mitigation and Adaptation Strategies for Global Change, 2015)

Distribution system water age can create premise plumbing corrosion hotspots - Sheldon Masters; Jeffrey Parks; Amrou Atassi; Marc A. Edwards (Environmental Monitoring and Assessment, 2015)

Recovery of precision grasping after motor cortex lesion does not require forced use of the impaired hand in macaca mulatta - Warren G. Darling; Robert J. Morecraft; Diane L. Rotella; Marc A. Pizzimenti; Jizhi Ge; Kimberly S. Stilwell-Morecraft; Hongyu Zhang; Hesham Soliman; Dave Seecharan; Ian Edwards; David McNeal; Randolph J. Nudo; et al. (Experimental Brain Research, 2014)

Monitoring physiological stress in semi-free ranging populations of an endangered Australian marsupial, the Greater Bilby (Macrotis lagotis) - Edward J. Narayan; Nicole Evans; Jean-Marc Hero (European Journal of Wildlife Research, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

The global contribution of forage fish to marine fisheries and ecosystems - Ellen K Pikitch; Konstantine J Rountos; Timothy E Essington; Christine Santora; Daniel Pauly; Reg Watson; Ussif R Sumaila; P Dee Boersma; Ian L Boyd; David O Conover; Philippe Cury; Selina S Heppell; et al. (Fish and Fisheries, 2014)
Forage fish play a pivotal role in marine ecosystems and economies worldwide by sustaining many predators and fisheries directly and indirectly. We estimate global forage fish contributions to marine ecosystems through a synthesis of 72 published E copath models from around the world. Three distinct contributions of forage fish were examined: (i) the ecological support service of forage fish to predators in marine ecosystems, (ii) the total catch and value of forage fisheries and (iii) the support service of forage fish to the catch and value of other commercially targeted predators. Forage fish use and value varied and exhibited patterns across latitudes and ecosystem types. Forage fish supported many kinds of predators, including fish, seabirds, marine mammals and squid. Overall, forage fish contribute a total of about $16.9 billion USD to global fisheries values annually, i.e. 20% of the global ex‐vessel catch values of all marine fisheries combined. While the global catch value of forage fisheries was $5.6 billion, fisheries supported by forage fish were more than twice as valuable ($11.3 billion). These estimates provide important information for evaluating the trade‐offs of various uses of forage fish across ecosystem types, latitudes and globally. We did not estimate a monetary value for supportive contributions of forage fish to recreational fisheries or to uses unrelated to fisheries, and thus the estimates of economic value reported herein understate the global value of forage fishes.

Coagulation With Hydrolyzing Metal Salts: Mechanisms and Water Quality Impacts - Christina C. Davis; Marc Edwards (Critical Reviews in Environmental Science and Technology, 2014)

Do mutator mutations fuel tumorigenesis? - Edward J. Fox; Marc J. Prindle; Lawrence A. Loeb (Cancer and Metastasis Reviews, 2013)

Oviposition Threshold for Flight in an Inter-Reproductive Migrant Moth - Marc Rhainds; Edward G. Kettela (Journal of Insect Behavior, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Lead (Pb) quantification in potable water samples: implications for regulatory compliance and assessment of human exposure - Simoni Triantafyllidou; Caroline K. Nguyen; Yan Zhang; Marc A. Edwards (Environmental Monitoring and Assessment, 2013)

Lead (Pb) in Tap Water and in Blood: Implications for Lead Exposure in the United States - Simoni Triantafyllidou; Marc Edwards (Critical Reviews in Environmental Science and Technology, 2012)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

A proposal to change existing virus species names to non-Latinized binomials - Marc H. V. Van Regenmortel; Donald S. Burke; Charles H. Calisher; Ralf G. Dietzgen; Claude M. Fauquet; Said A. Ghabrial; Peter B. Jahrling; Karl M. Johnson; Michael R. Holbrook; Marian C. Horzinek; Günther M. Keil; Jens H. Kuhn; et al. (Archives of Virology, 2010)

PCR primers for microsatellite loci in a Madagascan waterbird, the Sakalava Rail (Amaurornis olivieri) - Edward G. Brede; Peter Long; Sama Zefania; Marc Rabenandrasana; Tamás Székely; Michael Bruford (Conservation Genetics Resources, 2010)

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Estimation of genetic parameters and prediction of breeding values for apple fruit-quality traits using pedigreed plant material in Europe - Abou Bakari Kouassi; Charles-Eric Durel; Fabrizio Costa; Stefano Tartarini; Eric van de Weg; Kate Evans; Felicidad Fernandez-Fernandez; Ceri Govan; Anastasia Boudichevskaja; Frank Dunemann; Adriana Antofie; Marc Lateur; et al. (Tree Genetics & Genomes, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Nitrification in Drinking Water Systems - Yan Zhang; Nancy Love; Marc Edwards (Critical Reviews in Environmental Science and Technology, 2009)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

The Importance of Temperature in Assessing Iron Pipe Corrosion in Water Distribution Systems - Laurie S. McNeill; Marc Edwards (Environmental Monitoring and Assessment, 2002)

Assessing genetic diversity of sweet potato (Ipomoea batatas (L.) Lam.) cultivars from tropical America using AFLP - Dapeng Zhang; Jim Cervantes; Zosimo Huamán; Edward Carey; Marc Ghislain (Genetic Resources and Crop Evolution, 2000)

Reversible inactivation of macaque dorsomedial frontal cortex: effects on saccades and fixations - Marc A. Sommer; Edward J. Tehovnik (Experimental Brain Research, 1999)